Scaling bioethanol for the future: the commercialization potential of extremophiles and non-conventional microorganisms - Mohammed Al-Hammadi; Günsu Anadol; Francisco José Martín-García; Jaime Moreno-García; Tuğba Keskin Gündoğdu; Mine Güngörmüşler (Frontiers in Energy Research)
Unlike conventional bioethanol production, which raises environmental concerns such as a high carbon footprint from resource-intensive crops, deforestation, and food security issues, non-conventional bioethanol production offers a more sustainable alternative. However, non-traditional feedstock availability and its pretreatment are the main challenges, importantly feedstock availability is either underreported or poorly forecasted, while pretreatment is costly, reaching up to 40% of the overall process or it might generate inhibitors that hamper ethanol production in commercial scale, as well as environmental impact. The literature further lacks the recent update for conventional and non-conventional microbial ability to ferment these feedstocks or their tolerance for inhibitors compared with the conventional yeast. Therefore, this review discusses Europe’s non-conventional feedstock availability in national levels and pretreatment, highlighting pretreatment’s cost industrially, scalability, and its impact on microbial fermentation and the environment. Moreover, recent European policies that might impact the commercialization of non-conventional bioethanol are discussed, emphasizing the revised RED III policy, certification scheme, and how to eliminate fraudulent biofuel imports to boost advanced ethanol production. Finally, this review discusses the pilot-scale case studies that investigated the non-conventional methods besides the recent update on non-conventional microbes’ ability, inhibitors, and the techniques such as the immobilization to improve ethanol yield.